Mycoses and mycotoxicosis in poultry: A review - Jand, S K; Kaur, Paviter; Sharma, N S (The Indian Journal of Animal Sciences, 2005)
Mycopathy is a collective term used for diseases caused by fungi. either living or dead or their metabolic products (toxins, allergins or enzymes). This complex term comprises disease manifestations e.g. mycoses, mycotic colonisation. myco-allergosis, mycetism and mycotoxicosis. Mycoses is a term used for fungal diseases in which the pathogens attack living tissues in a parasitic manner i.e. by spreading and multiplying in the tissue with destructive effects e.g. candidiasis (thrush), aspergillosis etc. Whereas mycotoxicosis is the disease syndrome produced by seconday metabolites of certain fungi infecting different feeds and their ingredients. Mycotoxins are currently considered as a serious threat to the poultry farming in terms of diseases leading to synergistic interactions with other infectious agents. Several mycotoxins have been high lightened as poultry feed contaminants e.g. aflatoxins. ochratuxins, trichothecenes, citrinin. sterigmatocystin and diacetoxyscirpenol (DAS). The most obvious effect of mycotoxins on poultry is mortality which is produced when high levels (&gt 800 µg KG¯¹) of aflatoxins are present in feeds. Exposure to moderate to low levels (200-800 µg KG¯¹) of aflatoxins over a considerable period of time leads to reduce productivity in (he form of slower rate of growth. reduced reproducibility and inferior quality of poultry products resulting in serious economic losses for broiler producers. Low concentrntions (50-200 µg KG¯¹) of aflatoxins in feed predispose the birds to infectious diseases through he impairment of immunogenesis and native mechanisms of resistance. A holistic approach is required to combat the adverse effects of mycotoxin to enhance the overall poultry production e.g, regular surveillance and monitoring of important mycotoxins through approved mycotoxin analytical laboratories using rapid, cost effective methods and use of economical and practical methods to eliminate, detoxify or destabilise the mycotoxins in feeds like use of hydrated sodium calcium aluminosilicate (HSCAS); zeolites, bentonites, clays and activated carbon.